Development and Implementation of Water Quality Assessment Monitoring (WQAM) System using the Internet of Things (IoT) in Water Environment - Johan, Muhammad Farhan; Abdullah, Samihah; Mohamad Hadis, Nor Shahanim; Omar, Saodah; Zanal, Asmalia (Journal of Electronic Voltage and Application, 2021)
Water quality assessment monitoring (WQAM) system are widely being explore as it is needed to prevent the problem with water contamination problem worldwide. Nowadays, there are various WQAM to be implement with the Internet of Things (IoT) for Wireless Sensor Network (WSN) technology to get real time data measurement. Gathering data, the traditional ways is more time consuming and it lacks the real time changes in the quality of water. This project will be presenting on using WiFi enabled microcontroller to be used to connect with the IoT environment and store the data in the IoT cloud server. The microcontroller to be use is Arduino UNO that will be interact with three types of sensor probe that is pH, turbidity and temperature. All the data measurement will be transferred using a WiFi module which is ESP8266. The IoT cloud that is to utilize the data frame is ThingSpeak. The implementation of this system is to take samples from different location of the surface water and identify if the readings are different according to the location. This system was used to take result on lake and river which later found that there is difference from both places. The water flow of surface water was concluded to take effect on the difference in readings for the test. As conclusion, this system would benefit the authorities to take advantage of using the WQAM system with the aid of the IoT that is less time consuming, costless and is more reliable in giving real time data reading.